Morphology and structure of acorn starches isolated by enzymatic and alkaline methods - Correia Paula M. R. (De Gruyter, 2021)
Morphology and structure of starch from fruits of two acorns species, Quercus rotundifolia Lam. (QR) and Quercus suber Lam. (QS), isolated by enzymatic (ENZ) and alkaline (A3S) methods were studied. Acorn starches granules presented a round and oval shape, consisting of medium/small granules, with a mean granule size ranging between 9 and 13 µm. Isolated acorn starches appear as light grayish-brown in naked eye, with high values of L* for starches isolated by the ENZ method, and QR starches were duller than QS. No differences were observed for all the samples in FTIR spectra results. Acorn starches showed a C-type pattern, with a relative crystallinity between 43.1 and 46.6%. The 13C CP/MAS NMR spectra are different for the used isolation methods but are similar for both acorn species. However, acorn-isolated starches presented a predominant A-type allomorph packing type, and the A3S starches showed a higher degree of crystalline material. Those differences in the structure of acorn starches would be helpful to better understand the relationships among structure and functional properties for a possible potential industrial application of chestnut starches.